Calcaneal Avulsion Fractures: A Multicenter Analysis of Soft-Tissue Compromise and Early Fixation Failure. Issue 11 (November 2019) - Mitchell, Phillip M.; O'Neill, David E.; Branch, Eric; Mir, Hassan R.; Sanders, Roy W.; Collinge, Cory A.
Abstract : Objective: To characterize the presentation and outcomes of calcaneal avulsion fractures. Design: Case series. Setting: Two ACS Level I trauma centers. Patients/Participants: Forty-seven calcaneal avulsion fractures isolated from a cohort of 1365 calcaneus fractures treated over a 17-year period. Main Outcome Measurements: We collected instances of soft-tissue compromise at presentation, evidence of implant failure or fracture displacement after fixation, and reoperation. Results: Forty-one patients were treated operatively, and 6 were treated without surgery. Twenty-one patients (44.7%) had either soft-tissue compromise or an open fracture necessitating urgent treatment at the time of presentation. Of those patients treated operatively with 3-month follow-up (n = 39), 28.2% of patients (11/39) had evidence of implant failure or fracture displacement. Age was the only predictor of catastrophic fixation failure ( P = 0.01). The use of washer(s), suture anchor(s), or addition of soft-tissue procedures (eg, Strayer) did not have a significant effect on failure rate. Neither the number of screws used nor size of screw impacted the failure rate. Fourteen patients (35.9%) underwent a secondary operation. Discussion: Avulsion fractures of the calcaneus commonly present with soft-tissue compromise and have a significant rate of treatment failure and reoperation. This injury should be identified early and approached thoughtfully, acknowledging that risks are high. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.